2020
DOI: 10.3390/ijerph17020580
|View full text |Cite
|
Sign up to set email alerts
|

Nomophobia: An Individual’s Growing Fear of Being without a Smartphone—A Systematic Literature Review

Abstract: This review examines the current literature focused on nomophobia (objectives, methodological design, main variables, sample details, and measurement methods) in the Scopus and Web of Science databases. To this end, we conducted a systematic literature review in accordance with the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines. The initial sample consisted of 142 articles, of which 42 met the inclusion criteria and were analyzed in detail. The findings show that the current research is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
112
0
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(177 citation statements)
references
References 60 publications
(272 reference statements)
9
112
0
21
Order By: Relevance
“…In a similar vein, the analysis of the relationship between issues through the Jaccard index allowed us to discern relevant connections between issues, as was the case with the one maintained between "prevalence-prevalence-depression-adolescent", "addiction-behavior-addiction-adolescent", or "online-loneliness-self-esteem". These links allowed us to corroborate the interest of the research community in the risks associated with ADIN over the years, an idea similar to those expressed in previous research [7,17,33,34]. Specifically, the main population under study, according to the works analyzed, are young people, especially adolescents.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In a similar vein, the analysis of the relationship between issues through the Jaccard index allowed us to discern relevant connections between issues, as was the case with the one maintained between "prevalence-prevalence-depression-adolescent", "addiction-behavior-addiction-adolescent", or "online-loneliness-self-esteem". These links allowed us to corroborate the interest of the research community in the risks associated with ADIN over the years, an idea similar to those expressed in previous research [7,17,33,34]. Specifically, the main population under study, according to the works analyzed, are young people, especially adolescents.…”
Section: Discussionsupporting
confidence: 83%
“…The way in which people interact with each other, entertain themselves, and consume through the media has been modified through the Internet [5]. However, as more people connect to multimedia devices to share information and make use of the possibilities they are offered, cases of media addiction are growing at a dangerous pace [6,7]. These addictions have grown significantly over the last decade [8], surpassing other types of addictions.…”
Section: Introductionmentioning
confidence: 99%
“…Although problematic mobile phone use has been explored throughout Australia [ 38 ], our study is the first to explore nomophobia among an Australian sample. This study consists of the second largest sample size ( n = 2838) in any nomophobia study to date [ 31 ], revealing a mean nomophobia score of 69.4 (moderate) among respondents. By comparison, a sample of over 3216 Iranian adolescents showed a mean nomophobia score of 74.65 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In short, the fear of being without a mobile phone has a relationship with psychometric traits that can lead to problematic behaviour; however, there is no research detailing whether nomophobia is actually problematic. Additionally, a recent systematic literature review of over 42 studies focused on nomophobia [ 31 ] found the condition exists globally; however, no studies have explored nomophobia is Australia.…”
Section: Introductionmentioning
confidence: 99%
“…This scientific mapping takes as main references, the h index and the number of citations [68], and as secondary indicators, the g, hg and q2 indexes [69], trying to offer as much information as possible about the metrics of the field of study [70]. Throughout this procedure, a PRISMA protocol has been applied to collect scientific output [71], and various criteria for inclusion in the control variables to show the results obtained [72].…”
Section: Methodsmentioning
confidence: 99%